Innate immunogenetic synergy between KIR and Neanderthal-derived OAS variants predicts COVID-19 outcomes - Hasan Yalim Akin; Timur Tuncali; Emine Begum Gencer; Guldane Cengiz Seval; Elif Mukime Saricaoglu; Ezgi Gulten; Irem Akdemir Kalkan; Gule Cinar; Osman Memikoglu; Ridvan Goksel Anliacik; Ezgi Anliacik; Ergun Karaagaoglu; et al. (PLoS ONE, 2026)
Background Genetic factors modulate the progression of coronavirus disease 2019 (COVID-19), but interactions between innate immune gene variants remain incompletely understood. Prior work identified Killer Immunoglobulin-like Receptor (KIR) genotypes and Neanderthal-introgressed OAS 1/2/3 haplotypes as key modulators of disease severity. Given these parallel findings, we aimed to evaluate the synergistic impact of KIR motifs, Neanderthal-inherited OAS 1/2/3 variants, and other immune-related SNPs on COVID-19 symptomatology and severity. Methods In a cohort of 175 unvaccinated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) positive individuals (65 asymptomatic, 47 mild-intermediate, 63 severe), we genotyped KIR/KIR-ligand motifs and variants in OAS 1/2/3, IFITM3 , DPP4 , TLR7 , and APOE . Multivariate logistic regression models assessed independent and interactive predictors of symptomatic and severe disease, and ROC curve analysis was performed to quantify their discriminative ability. Results An interaction between the absence of both the protective tAB1/wL KIR motif and the Neanderthal-derived OAS 1/2/3 alleles significantly predicted symptomatic infection (OR 3.47, P = 0.006) and severe disease (OR 2.41, P = 0.038), achieving overall classification accuracies of 75.4% and 78.9%, respectively. Independent predictors included age, male gender, rs12252 ( IFITM3 ) and rs3788979 ( DPP4 ) as risk factors, and blood group A and APOE ε3ε3 status as protective factors. No rare TLR7 variants were detected. Conclusion This study identifies, for the first time, a synergistic interaction between KIR motifs and Neanderthal-derived OAS 1/2/3 variants influencing COVID-19 outcomes. These findings highlight the interplay between ancient and modern innate immune adaptations in shaping viral disease susceptibility. Future studies in larger and diverse populations are warranted to validate these immunogenetic interactions.